2005
DOI: 10.1088/0957-4484/16/6/016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticle surface modification on the electrical behaviour of polyethylene nanocomposites

Abstract: In this study, we present the results of the influence of surface modification of TiO2 nanoparticles on the short-term breakdown strength and space charge distribution of low-density polyethylene (LDPE). A polar silane coupling agent N-(2-aminoethyl) 3-aminopropyl-trimethoxysilane (AEAPS) was used for the nanoparticle surface modification. Despite agglomeration and a poor interface compared to untreated nanoparticles, it was found that the incorporation of polar groups onto the nanoparticle surface improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(149 citation statements)
references
References 43 publications
4
141
0
4
Order By: Relevance
“…8,9 These states are highly dependent on the chemistry of nanoparticle surface modification. 10 Surface modification is silicon based; it creates a stable bonding between nanoparticles and polymer and contributes to a) Electronic mail: elena.kubyshkina@ee.kth.se b) Also affiliated with KTH Royal Institute of Technology, School of Chemical Science and Engineering, Fibre and Polymer Technology, Stockholm SE-100 44, Sweden.…”
mentioning
confidence: 99%
“…8,9 These states are highly dependent on the chemistry of nanoparticle surface modification. 10 Surface modification is silicon based; it creates a stable bonding between nanoparticles and polymer and contributes to a) Electronic mail: elena.kubyshkina@ee.kth.se b) Also affiliated with KTH Royal Institute of Technology, School of Chemical Science and Engineering, Fibre and Polymer Technology, Stockholm SE-100 44, Sweden.…”
mentioning
confidence: 99%
“…The treated silica agglomerates showed nucleating effect and reduced the size and perfection of the spherulites, and the measurement of water contact angle also indicated great difference between the treated and untreated silica nanocomposites [88]. The breakdown strength of treatedTiO 2 /LDPE showed a nearly 40% increase than that of as-received nanoscale TiO 2 -filled specimens [89]. These results mean that the surface condition of nanoparticles is the dominant factor to determine the macroscopic performances of nanodielectrics.…”
Section: Discussionmentioning
confidence: 85%
“…11 12 Muszynska et al 13 have demonstrated an overall increase in conductivity of a polyethylene oxide matrix using Al filler nanoparticles in concentration range 0.25-5 wt%. Beyond this miniscule range a decrease in conductivity is observed.…”
Section: Introductionmentioning
confidence: 99%